Fabrication of ultrafine manganese oxide-decorated carbon nanofibers for high-performance electrochemical capacitors. (1st September 2016) - Yang, Ying; Lee, Sungsik; Brown, Dennis E.; Zhao, Hairui; Li, Xinsong; Jiang, Daqiang; Hao, Shijie; Zhao, Yongxiang; Cong, Daoyong; Zhang, Xin; Ren, Yang
Graphical abstract: Morphology controlled synthesis of Mn, Zn-containing metal organic framework fibers was carried out by varying the assembly time. Such a fiber precursor was converted to a new type of ultrafine manganese oxide-decorated carbon nanofiber upon pyrolyzed. This synthesis integrates excellent accessibility, high porosity, tight contact and superior conductivity in the final products, and thus exhibits a remarkable capacitance of up to 18290 F g −1 per active mass of the manganese(IV) oxide, high stability of cycling up to 5000 times, as well as the maximum energy density is up to 19.7 Wh kg −1 at the current density of 0.25 A g −1 . Highlights: Facile synthesis of MnOn -CNF composites by construction and evolution of Mn-ZnBTC fibers. Excellent accessibility, high porosity, tight contact and superior conductivity are integrated. Remarkable capacitance of up to 18290 F g −1 per active mass of the manganese(IV) oxide. Superior stability of cycling up to 5000 times with a high capacitance retention ratio of 98%. Abstract: Ultrafine manganese oxide-decorated carbon nanofibers (MnOn -CNF, 1.3 < n < 2.0) as a new type of electrode materials are facilely fabricated by direct conversion of Mn, Zn-trimesic acid (H3 BTC) metal organic framework fibers (Mn-ZnBTC). The construction and evolution of Mn-ZnBTC fibers are investigated by SEM and in situ high-energy XRD. The manganese oxides are highly dispersed onto the porous carbon nanofibers formed simultaneously, verified by TEM, X-ray absorption fine structure (XAFS), Raman, ICP-AES and N2 adsorption techniques. As expected, the resulting MnOn -CNF composites are highly stable, and can be cycled up to 5000 times with a high capacitance retention ratio of 98% in electrochemical capacitor measurements. They show a high capacitance of up to 179 F g −1 per mass of the composite electrode, and a remarkable capacitance of up to 18290 F g −1 per active mass of the manganese(IV) oxide, significantly exceeding the theoretical specific capacitance of manganese(IV) oxide (1370 F g −1 ). The maximum energy density is up to 19.7 Wh kg −1 at the current density of 0.25 A g −1, even orders higher than those of reported electric double-layer capacitors and pseudocapacitors. The excellent capacitive performance can be ascribed to the joint effect of easy accessibility, high porosity, tight contact and superior conductivity integrated in final MnOn -CNF composites.